Pemikiran Pembaharuan Muhammad Iqbal dalam Kajian Hermenutika Hadis - Bistara, Raha; Hadziq, Abdulloh (JURNAL AL-AQIDAH, 2024)
This article wants to explain the framework of Muhammad Iqbal's thinking in studying the renewal of Islamic knowledge in the form of hadith, in this case from a hermenutics perspective. Of course, what Muhammad Iqbal did received responses from two different sides in the form of those who agreed with the reform framework and those who did not agree with the reform framework, especially with the word hermeneutics. Those who do not agree with the heremeneutical framework prioritize the takwil framework, but in this case it is not that meaning that is discussed in this article but what is discussed is the hermeneutic framework. By using the library research method using primary sources written directly by Muhammad Iqbal and adding secondary sources in data processing, researchers found that the hadith conveyed by the Prophet must be able to be explained using a hermeneutical framework that is appropriate to social conditions. So, the meaning associated with hadith must be sought again within the framework of hermeneutics as a modern science. The hermenutics of hadith that must be understood is hadith hermeneutics, not the transfer of hadith texts to a new context arbitrarily, otherwise the hadith texts would be static and devoid of change. But what Muhammad Iqbal wanted was that the text must live up to the times. Where hadiths that do not fit into the framework of change and cannot keep up with the times do not have to be followed.